And they just keep coming: four new genera of dark sac spiders from southern Africa (Araneae, Trachelidae) - Haddad, Charles R. (Pensoft Publishers, 2025)
As part of ongoing revisions of the Afrotropical 𝘛𝘳𝘢𝘤𝘩𝘦𝘭𝘪𝘥𝘢𝘦, four new genera are described from southern Africa: 𝘍𝘰𝘰𝘳𝘥𝘢𝘯𝘢 𝗴𝗲𝗻. 𝗻𝗼𝘃., with 𝘍. 𝘥𝘪𝘴𝘵𝘪𝘯𝘤𝘵𝘢 𝘀𝗽. 𝗻𝗼𝘃. from South Africa (Eastern Cape, Free State, KwaZulu-Natal and Western Cape) as the type species, 𝘍. 𝘧𝘭𝘢𝘷𝘪𝘱𝘰𝘥𝘢 𝘀𝗽. 𝗻𝗼𝘃. from the Free State, 𝘍. 𝘬𝘢𝘴𝘰𝘶𝘨𝘢 𝘀𝗽. 𝗻𝗼𝘃. from the Eastern Cape and KwaZulu-Natal, and a fourth undescribed species from Zimbabwe; the monotypic 𝘔𝘶𝘴𝘩𝘪𝘮𝘢𝘯𝘦 𝗴𝗲𝗻. 𝗻𝗼𝘃., with 𝘔. 𝘵𝘴𝘸𝘪𝘣𝘪𝘭𝘪𝘯𝘬𝘪 𝘀𝗽. 𝗻𝗼𝘃. from KwaZulu-Natal as the type species; 𝘕𝘢𝘮𝘢𝘲𝘶𝘦𝘭𝘭𝘢 𝗴𝗲𝗻. 𝗻𝗼𝘃., with 𝘕. 𝘢𝘳𝘪𝘥𝘢 𝘀𝗽. 𝗻𝗼𝘃. from the Northern Cape as the type species and 𝘕. 𝘴𝘢𝘮𝘢𝘯𝘵𝘩𝘢𝘦 𝘀𝗽. 𝗻𝗼𝘃. from the Western Cape; and 𝘙𝘶𝘬𝘶𝘭𝘶𝘬 𝗴𝗲𝗻. 𝗻𝗼𝘃. from South Africa, with 𝘙. 𝘨𝘳𝘢𝘮𝘪𝘯𝘦𝘶𝘴 𝘀𝗽. 𝗻𝗼𝘃. from the Northern Cape as the type species and a second undescribed species from KwaZulu-Natal known only from juveniles.
Keywords: Grass; New species; Tree canopies